How does the media portray drinking water security in Indigenous communities in Canada? An analysis of Canadian newspaper coverage from 2000-2015 - Steven Lam; Ashlee Cunsolo; Alexandra Sawatzky; James Ford; Sherilee L. Harper (BMC, 2017)
Abstract Background Drinking water insecurity and related health outcomes often disproportionately impact Indigenous communities internationally. Understanding media coverage of these water-related issues can provide insight into the ways in which public perceptions are shaped, with potential implications for decision-making and action. This study aimed to examine the extent, range, and nature of newspaper coverage of drinking water security in Canadian Indigenous communities. Methods Using ProQuest database, we systematically searched for and screened newspaper articles published from 2000 to 2015 from Canadian newspapers: Windspeaker, Toronto Star, The Globe and Mail, and National Post. We conducted descriptive quantitative analysis and thematic qualitative analysis on relevant articles to characterize framing and trends in coverage. Results A total of 1382 articles were returned in the search, of which 256 articles were identified as relevant. There was limited coverage of water challenges for Canadian Indigenous communities, especially for Métis (5%) and Inuit (3%) communities. Most stories focused on government responses to water-related issues, and less often covered preventative measures such as source water protection. Overall, Indigenous peoples were quoted the most often. Double-standards of water quality between Indigenous and non-Indigenous communities, along with conflict and cooperation efforts between stakeholders were emphasized in many articles. Conclusion Limited media coverage could undermine public and stakeholder interest in addressing water-related issues faced by many Canadian Indigenous communities.